CULTURA ESCOLAR CATÓLICA NO SUL DO ANTIGO MATO GROSSO: EM FOCO O CURSO SECUNDÁRIO NAS INSTITUIÇÕES ESCOLARES SALESIANAS (1931–1961) - HELOISE VARGAS DE ANDRADE (2021)
In this paper we attempt to identify and understand school, social, cultural and religious practices in secondary confessional courses implemented by the Salesian congregation, in the South of the former Mato Grosso state, between the years of 1931-1961, in order to understand how the Salesian catholic school culture built provisions which worked on the structuring of a Salesian habitus. For this purpose the following investigated institutions were taken into account: Colégio Dom Bosco and Colégio Nossa Senhora Auxiliadora, sited in the city of Campo Grande; in addition Ginásio Santa Teresa and Ginásio Nossa Senhora Imaculada da Conceição, in the city of Corumbá. This research is linked to the research line – Education, Culture, Society, from the graduate studies program in Education, from the Education School, from the Federal University of Mato Grosso do Sul and dabbled in History and Sociology of Edutation, in order to approach the catholic school culture produced in interior of those secondary courses of these institutions. The year of 1931 is marked by Francisco Campos Reform, which stablished the basis of school culture in secundary teaching, also in the same decade Salesian institutions aforementioned started working concurrently. The year of 1961 is marked by the Law of guidelines and basis of Education, in which among other things was responsible for a lowering in humanistic disciplines and an advancement in a pedagogical technicist tendency. From this decade forward, Salesians started facing greater competition due to the fact of an increase of public institutions of secondary teaching. For such investigation sources we used school documents from the aforementioned institutions, memorial works, containing teachers and former students’ reports, journalistc sources about the those schools activities at the time, and local and national legislative documents about secundary teaching. Sources were analysed and crossed starting with Pierre Bourdieu’s theoretical background and interlocutors. For such analyse we based it on the concepts of school and religious field, practice and habitus. The school culture understading was used for approaching these educators trajectory in the Brazilian educational field and the Salesian educational ideals, which are systematized in the ‘Dom Bosco’s Preventive System’. The Salesians applied strategies in order to build an excellence education, along with pedagogical practices based on religious principles, that gave the congregation a legitimacy status in the educational field. Those schools invested in a religious and moral education which provided an approximation of the ‘legit culture’ and an expansion of simbolic and social capital. The results point out evidence that those practices contribuited in the structuring of a Salesian habitus – stablishing a particular worldview and way of being in society. The Salesian teaching contributed to the formation of methodical, religious and highly organized agents among other social attributes.